1984
DOI: 10.1128/jb.158.2.689-695.1984
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous transduction of phi 11de in Staphylococcus aureus: transfer and genetic properties

Abstract: The staphylococcal plasmid phi 11de is capable of transduction in the absence of both a helper bacteriophage and detectable plaque-forming bacteriophage. The mechanism of transfer is distinct from generalized transduction in that it does not transduce chromosomal material and is selective with respect to the plasmid DNA that is transduced. The transductants containing phi 11de have the following characteristics: (i) erythromycin resistance at levels displayed by the donor, (ii) expression of and susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…ate stringency. The membrane was dried at 80°C for 10 min and then autoradiographed as previously described (10). It is important to note that plasmid vectors pBR322 and pHV33 share no homology (with the wash stringency used here) with the genomes of S. aureus PS54 and PS54C or bacteriophages L54a or L54b.…”
Section: Methodsmentioning
confidence: 99%
“…ate stringency. The membrane was dried at 80°C for 10 min and then autoradiographed as previously described (10). It is important to note that plasmid vectors pBR322 and pHV33 share no homology (with the wash stringency used here) with the genomes of S. aureus PS54 and PS54C or bacteriophages L54a or L54b.…”
Section: Methodsmentioning
confidence: 99%
“…The purified phage was disrupted by suspending the bands in 2% sodium dodecyl sulfate and extracting twice for 15 min at 37°C with equal volumes of redistilled phenol equilibrated with 0.1 x SSC (1 x SSC is 0.15 M NaCl, 0.015 M sodium citrate, pH 7.0). The resulting DNA solution was then extracted twice with chloroform-isoamyl alcohol (24:1) and ethanol precipitated (4).…”
Section: Methodsmentioning
confidence: 99%
“…Hybridization analysis. Agarose gel electrophoresis and the procedures for Southern blot transfer and hybridization have been described by us (4). In certain instances, the double-blot procedure of Smith and Summers (25) was used to make mirror image blots of the same gel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phage, 44lde, which arose by in vivo recombination between 411 and the penicillin and erythromycin resistance (Pcr, Emr) plasmid p1258, acts more as a specialized transducing phage in being able to transfer the integrated Emr determinant at high frequencies; 4411de replicates as a plasmid through the presence of the p1258 replicon and is defective as a virus (345). More recently, it has been shown that 4llde is able to transduce the Cmr plasmid pC194, but not the neomycinkanamycin resistance (Nmr Kmr) plasmid pUB110 (112), and that particles able to cotransduce Cmr (pC194) and Emr (4llde) contained DNA composed of a linear multimer of approximately five copies of pC194 inserted randomly into the 411 genome (111).…”
Section: Staphylococcal Bacteriophages and Transductionmentioning
confidence: 99%